Coordinated Tracking for Nonlinear Multiagent Systems under Variable-Time Impulsive Control. (20th May 2019) - Tian, Yuan; Li, Chuandong; Yang, Xujun; Han, Yiyan
Abstract : This paper addresses variable-time impulsive control for coordinated tracking problem in nonlinear multiagent systems. To make followers coordinately track the leader, a variable-time impulsive controller is designed. Under some well-selected conditions, the comparison system of variable-time impulsive tracking control system is constructed by employing B-equivalence method. And we theoretically demonstrate that the two systems have the same stability property. Coordinated tracking criteria of multiagent systems are obtained by considering the comparison system. Numerical simulation is also provided to illustrate the correctness of theoretical results and the efficiency of the variable-time impulsive controller.